The Role of Mental Health Literacy in Burnout and Psychological Distress among University Students: A Systematic Literature Review - Hakim Anasulfalah; Rubiyanta; Ahmad Syauqi Mubarok; Joko Tri Atmojo; Rina Tri Handayani; Aris Widiyanto (Journal of Health Science Community, 2026)
This study aims to explore the role-mental health literacy on burnout and psychological distress in college students through a systematic literature review approach. The increasing phenomenon of mental health problems among college students is a significant concern because it impacts their psychological well-being, academic performance, and quality of life. This study used a descriptive qualitative approach with a systematic literature review method based on the PRISMA guidelines. Article searches were conducted through several online databases, namely PubMed, Scopus, ScienceDirect, BASE, and Consensus for the period 2020–2025. The article selection process was carried out using inclusion and exclusion criteria, resulting in 10 articles that met the requirements for analysis. Data were analyzed using thematic synthesis techniques to identify key research patterns and themes. The results showed that mental health literacy has a significant relationship with academic burnout, psychological distress, and psychological help-seeking behavior in college students. Students with good mental health literacy tend to have more adaptive coping skills, better emotional regulation skills, and are more open to seeking professional help when experiencing psychological problems. Conversely, low/mental health literacy is associated with increased stress, anxiety, emotional exhaustion, and academic burnout. This study concluded that mental health literacy is an important protective factor in maintaining students' mental health. These findings provide practical implications for universities to develop mental health promotion programs, psycho education, and campus-based counseling services to reduce the risk of burnout and psychological distress among students.